PENGAPLIKASIAN WEBGIS DALAM MEMBERIKAN INFORMASI PARIWISATA DI KABUPATEN TANAH DATAR - Aghnest Handika; Sri Mariya (JURUSAN GEOGRAFI FIS UNP, 2020)
This study aims to: 1) determine the distribution of Tourism Object, 2) apply WebGis, 3) determine the availability of facilities and infrastructure contained in Tourism Object in Tanah Datar District. This type of research is a descriptive study with a qualitative approach. Data collection techniques carried out by observation and documentation. Data analysis techniques are data reduction, data presentation, data verification and making reports. The results showed that: First, to determine the distribution of tourism objects in Tanah Datar District. Second, the availability of facilities and infrastructure products that exist in tourist objects in Tanah Datar District is still somewhat incomplete in some tourist attractions. Third, Geographic Information systems for Tourism Mapping in Tanah Datar based on WebGis can help in informing the public effectively and efficiently. This system displays the location with other supply components.